DEVELOPMENT OF THE METHOD OF APPLICATION OF THE EMITTER TO THE ELECTRODE DISCHARGE LAMPS BY VACUUMIZING - Ходурський, В. Є.; Ківа, О. В.; Китаєв, Є. В. (Scientific Progress & Innovations, 2014)
The article presents the results of work which was carried out to develop method of application of the emitter electrodes of discharge lamps by dipping them in a suspension of the emitter to the previous vacuumizing. Experimental studies were carried out on electrodes of lamps DRL-250 from the previous study the effect of evacuation on weight gain of the emitter, deposited on the electrode and the degree of filling of internal cavities emitter electrode on which it was proposed the technology of application to the emitter electrodes of discharge lamps with the previous vacuumizing . The article also gives results of experimental tests and obtained the comparative characteristics of methods for applying the emitterelectrodes in HID lamps known technology and by previous vacuumizing.